Legal Protection in Renting Villas by Foreign Nationals - DEVI, Ni Kadek Candra Nanda; SUWITRA, I Made; RENAYA, Nengah (Indonesia Strategic Sustainability, 2025)
The urgency of this research is to find certainty regarding the duration of the lease and the position of foreign citizens in the transfer of lease rights. Therefore, the relevant issues discussed are the civil responsibilities of the party transferring the lease rights concerning objects that are still under lease, and the legal protection that should be provided to good-faith tenants. The research method used is a normative legal method with legislative, analytical, and case study approaches, and the analysis of the legal materials used is an analysis based on content. The research results show that foreign nationals who transfer lease rights without a valid legal basis are civilly liable for the losses incurred, whether through compensation mechanisms, lawsuits for breach of contract, unlawful acts, or annulment of documents. Meanwhile, a good faith tenant, who obtains rights legally and is unaware of any legal defects, is entitled to legal protection based on the principles of justice and legal certainty. Therefore, it is recommended that notaries can design the lease period and residence permits for the foreign nationals, and in case of disputes, judges are expected to provide legal certainty and protection for good faith tenants.